2009
DOI: 10.1016/j.radonc.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of thoracic toxicity in palliative paraspinal single-fraction stereotactic body radiation therapy

Abstract: Background There has been an increase in the utilization of single-fraction stereotactic body radiation therapy (SBRT) to treat thoracic structures, but there have been few reports describing toxicity outcomes with this treatment. Methods We evaluated 119 sites (114 patients) with no prior history of thoracic radiation were treated from 10/1/2003 to 10/27/2008 with single-fraction SBRT to thoracic structures. The median dose to the gross tumor volume was 2400 cGy (range 1800–2400 cGy), as was the median dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The guidelines of dose constraints for the esophagus in single-fraction SBRT in Memorial Sloan-Kettering Cancer Center were as follows: level 1 dose constraint of esophagus is 15 Gy/2 mL, while level 2 is 20 Gy/2 mL [11], which are consistent with our findings. Timmerman [12] recommended dose constraints of esophagus for single-fraction SBRT to be 14.5 Gy to less than 5 mL (endpoint ≥ grade 3).…”
Section: Discussionsupporting
confidence: 89%
“…The guidelines of dose constraints for the esophagus in single-fraction SBRT in Memorial Sloan-Kettering Cancer Center were as follows: level 1 dose constraint of esophagus is 15 Gy/2 mL, while level 2 is 20 Gy/2 mL [11], which are consistent with our findings. Timmerman [12] recommended dose constraints of esophagus for single-fraction SBRT to be 14.5 Gy to less than 5 mL (endpoint ≥ grade 3).…”
Section: Discussionsupporting
confidence: 89%
“…Other series have reported similar parameters predictive for injury (16, 17). Gomez et al reported an early low rate of esophageal toxicity with single-fraction intrathoracic SRS (11). This analysis was limited by a small cohort and limited dosimetric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the cohort, dose-volume constraints for esophagus were at the discretion of attending physicians. After analysis of initial toxicity (11), formal dose-volume limits were instituted, with ≤15 Gy permissible to 2 cm 3 of esophagus. If not achievable, the limit could be increased to no more than 20 Gy to 2 cm 3 at the discretion of the attending physician.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing to spinal cord, the dose constraints to the esophagus in spinal SRS/SBRT are less understood. Even though the dose constraint standard has yet been established for esophagus, partial volume constraints, such as dose to a small volume of 1 to 5 cc (D1 cc to D5 cc), and Dmax have been suggested in previous reports and used in clinical trials 18, 19, 20. Unlike a point dose, such as Dmax to the cord, which is unlikely to be effected by the extra vertebrae, a partial volume parameter, like D1 cc, generally increases with move critical structure volume receiving dose.…”
Section: Discussionmentioning
confidence: 99%